The performance analysis of a unicast network when two protocols, SCTP (Stream Control Transmission Protocol) and TCP (Transmission Control Protocol) coexist in the network - Budiardjo, Bagio; Thiotrisno, Michael (UI Scholars Hub, 2003)
This paper elaborates the performance analysis of a unicast network when two protocols, SCTP (Stream Control Transmission Protocol) and TCP (Transmission Control Protocol) coexist in the network. These two protocols are tested using File Transfer Protocol (FTP) and Constant Bit Rate (CBR) based traffic. From the simulations, it could be concluded that SCTP could achieve better throughput compared to TCP in both FTP and CBR based traffic, with sufficiently high fairness index of both intrafairness and interfairness. The increase of simulation time yields to the increase and relatively stable network performance. The increase of the number of sessions of small bandwidth applications resulted in the increase of troughput and link utilization. The simulations show that implementation of SCTP and TCP in a unicast network generally could be done without having to degrade the network performance, with relatively high fairness index, over 0.85 for various traffic variations.